The case of Sherlock Holmes : secrets and lies in Conan Doyle's detective fiction - Glazzard, Andrew, 1970- (Edinburgh University Press, 2018)
The Case of Sherlock Holmes uncovers what is untold, partly told, wrongly told, or deliberately concealed in Arthur Conan Doyle's Sherlock Holmes saga.